PERAN KELOMPOK NELAYAN DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT NELAYAN DI KELURAHAN MUARAREJA KECAMATAN TEGAL BARAT KOTA TEGAL - Putri, Dede Ayu Andika; Setyowati, Retno; Wibowo, Agung (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
Muarareja Village, West Tegal District, Tegal City is one of the areas in Indonesia whose people still work as fishermen, especially small fishermen. The fishing community in Muarareja Village has a network or group called The Joint Venture Group. The purpose of this study is to find out the role of fishing groups in improving the welfare of fishing communities in Muarareja Village, West Tegal District, Tegal City. The basic method used using qualitasive method with analysis using miles and huberman method and validation using data source triangulation technique and triangulation methodology. Based on research, fishermen's groups not only serve as a means of distribution of assistance from the government but also play a role in improving the ability of fishermen in organizing and improving welfare.